Nurse's action in the prevention and early detection of uterine cancer in primary care: a scoping review (Research, Society and Development, 2022)
Objective: To analyze the scientific evidence on the role of nurses in the prevention and early detection of uterine cancer in primary care. Methodology: This is a scoping review, this study uses knowledge synthesis and grouping of data, a method that allows finding the main concepts about the nurse's role in the prevention and early detection of uterine cancer. The PCC and the PRISMA flowchart were used as a search strategy to report the selection process of the studies.  Expected results: The results were analyzed and it was found that there is still a considerable number of women who do not know the causes of uterine cancer, the purpose of the preventive exam; and associate the exam as something to be done when there is some abnormality; who do not perform the exam on a regular basis and who perform the exam only due to gynecological complaints. Conclusion: Nurses should continue working on health education with these patients, in a way that makes them aware of the importance of regularly performing this exam, whether through routine consultations, lectures, health campaigns, or other strategies that seek to draw the attention of these women to this estimate.